Holy Week at the Chapel of the Dukes of Braganza, A Capella Portuguesa, dir. Owen Rees - Moody, Ivan (Revista Portuguesa de Musicologia, 2014)
Recensão: Holy Week at the Chapel of the Dukes of Braganza, A Capella Portuguesa, dir. Owen Rees